Design and Analysis the Strength of the Structure Fixed Wing Vertical Take Off-Landing UAV - Santoso, Djarot Wahju; Putra, Aditya Nurcholis (SENATIK STT Adisutjipto, 2018)
To respond to traffic conditions in the city traffic jam so as to resolve the density it is necessary to observe these conditions which are monitored at all times. For this reason, it is necessary to design UAV (Unmanned Aerial Vehicle) that is capable of flexible maneuvering, which can take off and land vertically and move quickly to reach traffic in different places. The stages of research for designing fixed wing VTOL aircraft are carried out determining the geometry of the aircraft as the desired criteria, the analysis stage by 3D modeling with CATIA software. Simulation of structural analysis in the form stress and calculating the Margin of Safety from this design. The results of the aircraft design have 1.32 m fuselage length, 1.71 m wing span and aircraft weight 2.865 kg. The results of the analysis show that the aircraft structure is safe in cruise and vertical take-off load.